An Inspired-TBLT Framework to Enhance Students’ Speaking Performances in EFL Context - Irfan Fajrul Falah; Didi Suherdi; Ahmad Bukhori Muslim (Journal of English Education and Teaching, 2023)
As one of the pedagogical approaches, TBLT has been employed by both researchers and practitioners to develop students’ language skills in the last decades. Besides solid grounding theory that possessed, it demands the students to participate actively as well during the class. Its’ flexibility gives the teacher more freedom to integrate it into their teaching. However, only a few studies have been conducted in terms of integration or modification. The current study aimed at developing a framework inspired by TBLT to enhance students' speaking performances. It examines the effect of TBLT modification in the context of EFL in Indonesia, particularly speaking. It is a mixed method study where students (n-91) from two universities in Kuningan, West Java, Indonesia participated. Two instruments were used for data collection, tests, and a questionnaire. The result shows that the framework inspired-TBLT could enhance students' speaking performances. It can be seen from the result of speaking proficiency where the average of the post-test (9,67) was higher than pre-test (8.19). In addition, statistically, the value Sig. two-tailed was 0.042 or < 0.05. It means that this framework influences students’ speaking performance almost in all components that were tested (vocabulary, grammar, fluency, and pronunciation). Furthermore, in terms of students’ perception, this framework has received positive responses from the students since this framework engaged and demanded the students to get involved during class activities.